Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-49
|View full text |Cite
|
Sign up to set email alerts
|

Does speech production in L2 require access to phonological representations?

Abstract: Following the theory of direct realism [1, 2, 3], non-native (L2) speakers should be able to imitate a stimulus without requiring the access to L2 phonological representations. In line with theories of working memory [4, 5], however, they should encounter difficulties in imitating a stimulus with L2 phonological structure at the point once phonetic information decayed and therefore phonological representations are required. In order to test the validity of these claims, the current study investigates L2 speake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The difference scores from the target stimuli in the low memory load condition suggest that participants did not imitate the phonetic details of the target tones correctly. Previous research on imitation of consonant length also showed little effect of memory load [24]. The less than expected effect of memory load could be because when waiting for imitation in the long interval condition, participants rehearsed internally, which reduced the decay of phonetic details perceived from the stimuli, thus diminishing the difference between two memory load conditions.…”
Section: Discussionmentioning
confidence: 76%
“…The difference scores from the target stimuli in the low memory load condition suggest that participants did not imitate the phonetic details of the target tones correctly. Previous research on imitation of consonant length also showed little effect of memory load [24]. The less than expected effect of memory load could be because when waiting for imitation in the long interval condition, participants rehearsed internally, which reduced the decay of phonetic details perceived from the stimuli, thus diminishing the difference between two memory load conditions.…”
Section: Discussionmentioning
confidence: 76%